Depósitos do pleistocénico superior e do holocénico na plataforma litoral da região do Porto : a morfologia das plataformas de erosão marinha e a tectónica recente - Araújo, Maria da Assunção (2014)
Upper Pleistocene and Holocene deposits in the coastal platform of the Porto region: the morphology of the marine platforms and neotectonics: the study of Quaternary sedimentary deposits of the coastal zone of Porto included a very detailed fieldwork and the accurate altitude definition with a GPS (Leica SR20). Luminescence dating of aeolian and lagoon deposits was performed to confirm our hypothesis about the deposits chronology and recent tectonic movements. However, the marine deposits can not be dated by TL and even OSL is quite problematic due to the small thickness of the beds. Our main goal is to characterize the several marine platforms along this coastline. It was possible to identify the present-day marine platform, some rare tiny Flandrian platform remains and also the more frequent and generally deposit bearing Eemien platform. This work has proved that even the last interglacial marine deposits have suffered some tectonic disturbance as they appear at quite different altitudes along this coastal zone.